2019
DOI: 10.1155/2019/2506843
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Immune-Associated Genes to Predict Survival in Clear Cell Renal Cell Cancer

Abstract: Background To elucidate the correlations between tumor microenvironment and clinical characteristics as well as prognosis in clear cell renal cell cancer (ccRCC) and investigate the immune-associated genes by a comprehensive analysis of The Cancer Genome Atlas (TCGA) database. Methods We collected mRNA expression profiles of 537 ccRCC samples from the TCGA database. Immune scores and stromal scores were calculated by applying the ESTIMATE algorithm. We evaluated the correlation between immune/stromal scores an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
5
45
0
Order By: Relevance
“…Current literature indicated that the recruitment of CD4 + T cells in tumor microenvironment could promote RCC proliferation and regulatory T cells can also inhibit tumor immune responses. [ 34 , 35 ] Hu et al reported that higher immune scores may predict the advanced TNM stage, [ 36 ] which is similar to our results. Additionally, we found that patients with lower immune scores tended to have lower stromal scores.…”
Section: Discussionsupporting
confidence: 91%
“…Current literature indicated that the recruitment of CD4 + T cells in tumor microenvironment could promote RCC proliferation and regulatory T cells can also inhibit tumor immune responses. [ 34 , 35 ] Hu et al reported that higher immune scores may predict the advanced TNM stage, [ 36 ] which is similar to our results. Additionally, we found that patients with lower immune scores tended to have lower stromal scores.…”
Section: Discussionsupporting
confidence: 91%
“…reprogramming described in diverse cancers which involve the overexpression of both HMGC2 (28,29) and PGC-1α transcripts (24). Overexpression of HMGC2/PGC-1α has been observed in high-grade colorectal cancer (30), colitisassociated cancer (31), clear cell renal cell cancer (32,33), ovarian (34), liver (35), oral squamous cell carcinoma (36) and high-grade prostate cancer (37), and is reflective of recurrence and poor prognosis (38). The dual induction of HMGCS2/PGC-1α also propels oncogenic mediated ketogenic events within the cancer milieu/stroma (for example, in cancer-associated fibroblasts) (39).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated score was also related to overall survival ( p = 0.0359) [ 16 ]. In ccRCC, a higher immune score was associated with shorter overall survival ( p = 0.04), and a close association was reported between immune scores, clinical characteristics, as well as prognosis in ccRCC [ 28 ]. These data indicate that TME plays an important role in tumorigenesis and prognosis.…”
Section: Discussionmentioning
confidence: 99%